Bulgaria : Request for Stand-By Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
Bulgaria's request for a 25-month precautionary Stand-By Arrangement (SBA) in an amount of SDR 100 million or 15.62 percent of quota is discussed. The SBA-supported program seeks to reduce increased external vulnerability and to achieve sustainable high growth through a tighter fiscal policy and measures to drain bank liquidity to reduce excess demand in the short term and structural reforms to boost output and export capacity in the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet